Gdy „życie staje się torturą, za którą podwójna niemoralność idzie”. Od małżeństwa do rozwodu w XIX i początkach wieku XX w Królestwie Polskim - Sikorska-Kowalska, Marta (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2011)
The paper presents a religious and civil regulations from law codexes concerning the principles of getting married and getting divorced. In particular, a characterization of Christian and Jewish marriages in the light of religious regulations is discussed, as well as the civil law regulations contained in the Codex of Napoleon and in the Civil Codex of the Kingdom of Poland. Also a discussion on the question of divorces which took place in the second half of the XIXth century in Warszawa press is presented.